Main guidelines in road safety audits: a literature review - Calderón Ramírez, Julio Alberto; Núñez López, Itzel; García Gómez, Leonel Gabriel; Montoya Alcaraz, Marco Antonio (Frontiers in Built Environment, 2023)
Road safety is a global issue, as each year more than 1.25 million people die in traffic accidents, and between 20 and 50 million suffer non-fatal injuries. Road Safety Audits (RSA) are implemented in different countries around the world. These audits involve a systematic process that includes an analysis to ensure that existing or future roads meet optimal safety criteria. In this context, the objective of this research is to identify the main guidelines applied in RSA through a literature review conducted using the PRISMA-ScR methodology. After grouping the guidelines, the ten most used worldwide are obtained, with four of them related to the human factor and six related to the road factor. The guidelines with the highest usage are those related to geometric design, signage, and safety devices. Finally, it is concluded that despite road accidents being an international issue faced by all countries, there is no clear or standardized methodology for the application of these audits. In other words, each country adopts its own method or checklist as a support tool for the team of auditors conducting RSA.